Modulating the Immune Response in Periodontitis - Bezerra, Beatriz; Monajemzadeh, Sepehr; Silva, Davi; Pirih, Flavia Q. (Frontiers in Dental Medicine, 2022)
Periodontitis is a chronic inflammatory condition initiated by the accumulation of bacterial biofilm. It is highly prevalent and when left untreated can lead to tooth loss. The presence of bacterial biofilm is essential for the initiation of the inflammatory response but is not the sole initiator. Currently it is unknown which mechanisms drive the dysbiosis of the bacterial biofilm leading to the dysregulation of the inflammatory response. Other players in this equation include environmental, systemic, and genetic factors which can play a role in exacerbating the inflammatory response. Treatment of periodontal disease consists of removal of the bacterial biofilm with the goal of resolving the inflammatory response; however, this does not occur in every case. Understanding the way the inflammatory response does not return to a state of homeostasis has led investigators to consider both systemic and local pharmacological interventions. Nonetheless, a better understanding of the impact that genetics and environmental factors may have on the inflammatory response could be key to helping identify how inflammation can be modulated therefore stopping the destruction of the periodontium. In this article we will explore the current evidence associating the microbial dysbiosis and the dysregulation of the immune response, potential mechanisms or pathways that may be targeted for the modulation of the inflammatory response, and discuss the advantages and drawbacks associated with local and systemic inflammatory modulation in the management of periodontal disease. This information will be valuable for those interested in understanding potential adjunct methods for managing periodontal diseases, but not limited to, dental professionals, clinical researchers and the public at large.